Effect of the High-Intensity Interval Training on BDNF Level in Ischemic Stroke Rat Model on the Recovery of Motor Function - Yani, Sri; Harris, Salim; Jusuf, Ahmad Aulia; Goenarjo, Roman; Makkiyah, Feda Anisah; Sabita, Rifqi; Ibrahim, Nurhadi (The Indonesian Biomedical Journal, 2024)
BACKGROUND: Stroke is one of the major causes of disability in the world. High-intensity interval training (HIIT) is known as a novel treatment to promote stroke recovery. However, the results differ in their effects on irisin, which is a regulator of brain-delivered neurotrophic factor (BDNF). Therefore, this study was conducted to investigate the effect of HIIT on BDNF and irisin levels in a rat model of ischemic stroke with middle cerebral artery occlusion (MCAO) induction on recovery motor function.METHODS: Rats were categorized into 4 groups: sham, MCAO, MCAO+moderate-intensity interval training (MIIT), and MCAO+HIIT. MCAO induction was performed to create the ischemic stroke rats model. The motor function was assessed through rotarod and footprint tests. Blood samples were obtained 6 days before MCAO and 14 days after MCAO to examine BDNF and irisin levels with enzyme-linked immunosorbent assay (ELISA). Brain tissue samples were collected 14 days after MCAO for histopathological examination of cortical tissue with hematoxylin-eosin (HE) staining.RESULTS: Rats in the MCAO+HIIT group exhibited an enhanced ability to walk on the rotarod (p=0.016). The stride-length hind paw right in the MCAO+HIIT group demonstrated a noteworthy increase in comparison to baseline value (p=0.036), and the stride-length fore paw right showed a significant increase in both the MCAO+HIIT (p=0.036) and MCAO groups (p=0.034). BDNF significantly improved in the MCAO+MIIT (p=0.043) and MCAO+HIIT groups (p=0.018). The irisin level only showed a significant enhancement in the MCAO+HIIT group (p=0.018).CONCLUSION: HIIT increased motor function, while BDNF level increased with HIIT and MIIT intervention. This preclinical research is useful for supporting the recovery of stroke patients by HIIT intervention.KEYWORDS: BDNF, HIIT, MIIT, irisin, ischemic stroke, MCAO